17.7k views
0 votes
Solve using any method. −2x+y=3 −3x+y=1 (-1, -2) (2, 7) (-2, -1) (-2, -5)

User Mum
by
6.3k points

1 Answer

3 votes

Answer:

Therefore the Final Solution is x = 2 and y = 7

i.e (2 ,7)

Explanation:

Given:


-2x+y=3 ...............Equation ( 1 )


-3x+y=1 ...............Equation ( 2 )


y=3x+1 ..............Equation ( 3 )

To Find:

x = ?

y = ?

Solution:

Substituting Equation ( 3 ) in Equation ( 1) we get


-2x+3x+1=3\\\\x=3-1\\\\\therefore x =2

Now Substituting x = 2 in Equation ( 3 ) we get


y=3* 2+1=6+1\\\\\therefore y=7

Therefore the Final Solution is x = 2 and y = 7

i.e (2 ,7)

User Ed Gibbs
by
6.0k points